1986
DOI: 10.1080/05698198608981699
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Detection of Synthetic Lubricant Oxidative Breakdown

Abstract: The oxidative breakdown of lubricating oils is accompanied by by monitoring volatile oxidation products with an electronic the liberation of vapor-phase oxidation products. A simple apparatus which uses a semiconducting tin oxide gas sensor has been employed to monitor the evolution of these products and determine the length of the induction period.The method provided reliable end-point detection with ester-base lubricants of moderate stability, simplifying the oxidation testing procedure and providing useful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Once the inhibitor concentration has fallen below a certain level, then the acid number, viscosity, and volatility of the oil all start to increase [ Figure 1]. This suggests that the use of a dielectric sensor (e.g., [22,23,46]), backed up by an electronic gas sensor [19,26,27], would provide confirming signals of the onset of oil degradation. Preliminary results [23] have shown that the dielectric constant decreases slowly during the useful life of the lubricant.…”
Section: Micmmachiningmentioning
confidence: 85%
See 1 more Smart Citation
“…Once the inhibitor concentration has fallen below a certain level, then the acid number, viscosity, and volatility of the oil all start to increase [ Figure 1]. This suggests that the use of a dielectric sensor (e.g., [22,23,46]), backed up by an electronic gas sensor [19,26,27], would provide confirming signals of the onset of oil degradation. Preliminary results [23] have shown that the dielectric constant decreases slowly during the useful life of the lubricant.…”
Section: Micmmachiningmentioning
confidence: 85%
“…The conductivity of the semiconductor increases significantly with increasing concentration of vapors and provides a dear signal of their presence. Ravner and Wohltjen [19] and Bolster and Wohltjen [26] have shown that this approach has merit. They demonstrated that an increase in gas evolution also marked the point at which the antioxidant was practically depleted and the acid number and viscosity were increasing rapidly.…”
Section: )mentioning
confidence: 99%